2019
DOI: 10.22159/ajpcr.2019.v12i1.30377
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial, and Antioxidant Activities of Two Moroccan Thymus Essential Oils

Abstract: Objective: The aim of the present study is to investigate chemical constituents of Thymus riatarum and Thymus blecherianus essential oils (EOs) as well as to evaluate, for the first time, their antioxidant effect and antibacterial activity against six bacterial strains responsible for nosocomial infections.Methods: The chemical composition of EOs was analyzed using gas chromatography (GC) and GC-mass spectrometry, the antibacterial capacity of the two thymus species was evaluated against six bacteria species: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Aerial parts of S. montana were collected from July to September 2013 in the locations from naturally growing populations in Albania and Montenegro [ 6 ]. Carvacrol and thymol are responsible for high antimicrobial activity of essential oils of S. montana and Thymus vulgaris [ 19 , 40 ]. According to B. Tepe and M. Cikiz, carvacrol is the main indicator of antimicrobial activity of essential oil [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aerial parts of S. montana were collected from July to September 2013 in the locations from naturally growing populations in Albania and Montenegro [ 6 ]. Carvacrol and thymol are responsible for high antimicrobial activity of essential oils of S. montana and Thymus vulgaris [ 19 , 40 ]. According to B. Tepe and M. Cikiz, carvacrol is the main indicator of antimicrobial activity of essential oil [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…The important antioxidant activity of the methanolic extract of Thymus leptobotrys to the DPPH and ABTS radical could be explained by its richness in phenolic compounds. There is indeed a correlation between the antioxidant activity and content of phenolic compounds [ 31 33 ]. On the other hand, many studies have reported that phenolic compounds are often known by their antioxidant activity [ 34 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using in vitro methods, Aouam et al [42] reported that Thymus riatarum showed a high DPPH radical-scavenging capacity and ferric reducing power in ethanolic, aqueous and methanolic extracts. In addition, Golkar et al [43] showed the cytotoxic activities of phenolic compounds in the essential oil of thyme by using a phosphomolybdate assay.…”
Section: Antioxidant Activity Of Thymementioning
confidence: 99%